Clinical and hemodynamic characteristics of patients with intermediate coronary lesions selected for elective percutaneous coronary intervention - M.V. Stan; К.О. Mikhaliev; A.V. Khokhlov; O.J. Zharinov; B.M. Todurov (Кардіохірургія та інтервенційна кардіологія)
The aim – to identify clinical, angiographic and hemodynamic factors, having impact upon the decision on percutaneous coronary intervention (PCI) in stable coronary artery disease (SCAD) patients with intermediate subepicardial coronary lesions, in clinical settings. Materials and methods. The cross-sectional single-center study analyzed clinical and instrumental data from 123 SCAD patients (mean age 62 ± 9 years; 90 (73.2 %) males) and intermediate (50–90 %) stenotic subepicardial coronary lesions (by invasive coronary angiography [ICA]). The enrolled sample included 74 (60.2 %) patients with an assessment of ICA-derived fractional flow reserve (FFR). The studied parameters were analyzed in the groups of decision not to perform (PCI(–); n = 30 [24.4 %]) and to perform PCI (PCI(+); n = 93 [75.6 %]). Results. The positive decision on PCI was more frequent in patients with stable angina ІII and ІI CCS class, as compared to those without angina (93 %, 79 % і 46 %, respectively; рtrend < 0.001). PCI was considered to be appropriate in all patients with FFR < 0.8 (46 of 74 (62 %) cases). The more advanced hemodynamic compromise of coronary lesions was associated with the higher maximum degree of coronary artery stenosis. Multivariable logistic regression analysis revealed a more pronounced coronary stenosis (at least, in one subepicardial coronary artery territory) was independently associated with the PCI(+) decision (stenosis 80–90 % vs. 70–79 %; 70–79 % vs. 60–69 %; 60–69 % vs. 50–59 %: odds ratio 26 (95 % confidence interval 8–87); р < 0.001). Conclusions. A degree of coronary artery stenosis was a key factor impacting upon a positive decision on PCI in SCAD patients with intermediate (50–90 %) coronary lesions. There is a need for the broader implementation of non-invasive diagnostic tests and the tools for a quantitative assessment of myocardial ischemia in patients with intermediate pretest probability of coronary stenosis, including those with previous PCI.